Floors - Carman, Patrick (New York : Scholastic Press, 2011)
Ten-year-old Leo's future and the fate of the extraordinary Whippet Hotel, where his father is the maintenance man, are at stake when a series of cryptic boxes leads Leo to hidden floors, strange puzzles, and unexpected alliances.
Keywords: Hotels and motels -- Fiction; Eccentrics and eccentricities -- Fiction; Puzzles -- Fiction